Estudio de las estrategias de difusión de las bandas de rock de la ciudad de Loja en las redes sociales facebook, youtube e instagram durante el periodo noviembre 2018, febrero 2019 - Villalta Abad, Jessenia Nohemy (2020)
This research is based on the study of outreach and diffusion strategies used by Loja City rock bands, specifically in the social networks Facebook, You Tube, and Instagram. This study was carried out due to the lack of support in the traditional means of communication: radio, television, newspapers, magazines and more. The current boom of social networks, which is a great support for using digital platforms today, has allowed musicians to manage them to promote and disseminate the work they are developing as artists, supported by these free networks and thus achieve the public and private companies support to work and live off it, something that is quite difficult today, since music is seen as a second option and not as the main source of income. Almost all musicians, have another kind of work, because in Loja can not only live off music. From this point of view, the respective research was carried out to know which are the found deficiencies and strengths in the strategies used by the rock bands, in this case was based on the study of 45 of them which were selected under the criteria of having their own material, being active, and not being cover bands.